PREDICTING BANKRUPTCY ON MINING COMPANIES USING ALTMAN Z-SCORE MODEL (EMPIRICAL STUDY ON MINING COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE YEAR 2014-2015) - Akhir, Husnul; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The aim of this study is to calculate Altman Z-Score to predict the possibility of bankruptcy of mining companies listed in Indonesia stock exchange based on the information from the annual financial statementwith observation ranging from 2014 until 2015. The type of data used is secondary data. The study employed Altmant Z-Score calculation on a targeted population of 22 mining companies listed on the Indonesia Stock Exchange.The analysis technique used is the prediction model of bankruptcy Altman Z-score. Using the formula Z-Score = 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 1,0X5, where X1 represents the ratio of liquidity, X2 and X3 as profitability ratios, and X4 and X5 are activity ratios. Then with the use of Z-Score assessment criteria 2.99 categorized as a very healthy company. 1.81 Z-Score 2.99 is in the grey area so the possibility of rescue and possibly bankrupt is as great as it depends on the decision of the company management policy as the decision maker. Zscore 1.81 is categorized as a company that has very large financial difficulties and high risk so that the possibility of bankruptcy is very large. The results show that in 2014, 55% of mining companies predicted bankruptcy, 18% are in grey area and the remaining 27% of mining companies have a healthy financial condition. Then in 2015, 64% of mining companies are predicted to go bankrupt, 23% are in grey area and 13% of companies are in good condition or not bankrupt.